6 − 4 = 
1
2
3
undefined

Minusaufgaben

8 − 2 = 1 − 1 =  2 − 1 =  3 − 1 =  3 − 1 =  4 − 1 =  6 − 1 =  8 − 1 =  5 − 1 =  7 − 1 =  9 − 1 =  10 − 1 =  10 − 0 =  9 − 0 =  8 − 0 =  7 − 0 =  6 − 0 =  5 − 0 =  4 − 0 =  3 − 0 =  2 − 0 =  1 − 0 =  0 − 0 =  2 − 2 =  3 − 2 =  4 − 2 =  5 − 2 =  6 − 2 =  7 − 2 =  8 − 2 =  10 − 2 =  9 − 2 =  3 − 3 =  4 − 3 =  5 − 3 =  6 − 3 =  7 − 3 =  8 − 3 =  9 − 3 =  10 − 3 =  4 − 4 =  5 − 4 =  6 − 4 =  7 − 4 =  8 − 4 =  9 − 4 =  10 − 4 =  5 − 5 =  6 − 5 =  7 − 5 =  8 − 5 =  9 − 5 =  10 − 5 =  6 − 6 =  7 − 6 =  8 − 6 =  9 − 6 =  10 − 6 =  7 − 7 =  8 − 7 =  9 − 7 =  10 − 7 =  8 − 8 =  9 − 8 =  10 − 8 =  9 − 9 =  10 − 9 =  10 − 10 = 

Schnellrechnen

3 + 2 = 1 + 2 = 4 + 5 = 4 + 4 = 6 + 4 = 5 + 5 = 2 + 8 = 2 + 2 = 3 + 3 = 1 + 7 = 1 + 1 = 2 + 4 = 4 + 1 = 0 + 1 = 0 + 10 = 3 + 4 = 2 + 1 = 2 + 5 = 2 + 6 = 2 + 7 = 1 + 1 = 1 + 3 = 1 + 5 = 6 + 1 = 8 + 1 = 1 + 9 = 3 + 5 = 3 + 6 = 3 + 7 = 4 + 2 = 4 + 6 = 5 + 3 = 5 + 4 = 5 + 5 = 5 + 2 =  5 + 0 =  0 + 4 =  0 + 3 =  0 + 2 =  0 + 0 =  6 + 0 =  0 + 7 =  0 + 8 =  0 + 9 =  6 + 2 =  6 + 3 =  7 + 2 =  7 + 1 =  8 + 1 =